2012
DOI: 10.1007/s10337-012-2231-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of Large Retention Index Database for Filtering of GC–MS False Positive Identifications of Compounds

Abstract: The use of the large retention index database for identification and filtering of false positive hits in GC-MS analysis of the ylang-ylang essential oil is illustrated. Differences between experimental retention indices and database values of retention indices of candidate compounds provide additional constraints on the list of candidates for a target compound. Over 100 components of ylang-ylang essential oil (total grade) were identified. The main components, with concentrations more than 4 %, are b-caryophyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
(34 reference statements)
0
14
0
Order By: Relevance
“…One microliter of diluted sample (split ratio 1/10) was injected into the GC at 250 • C with an autosampler (Shimadzu, Japan). The MS was operating in the electron impact mode (70 eV) at an interface temperature of 280 • C; the ion source temperature was 230 • C. The chemical components of essential oils were identified by matching their mass spectra to mass spectral libraries (NIST08.L and NIST08s.L) and comparing their retention indices to literature values (Babushok and Andriamaharavo, 2012;Djabou et al, 2012;Falco et al, 2013;Hosni et al, 2010;Sellami et al, 2012). The concentration of the identified compound was computed based on the percentage of the relative peak area (%).…”
Section: Essential Oils Analyses By Gc-ms Methodsmentioning
confidence: 99%
“…One microliter of diluted sample (split ratio 1/10) was injected into the GC at 250 • C with an autosampler (Shimadzu, Japan). The MS was operating in the electron impact mode (70 eV) at an interface temperature of 280 • C; the ion source temperature was 230 • C. The chemical components of essential oils were identified by matching their mass spectra to mass spectral libraries (NIST08.L and NIST08s.L) and comparing their retention indices to literature values (Babushok and Andriamaharavo, 2012;Djabou et al, 2012;Falco et al, 2013;Hosni et al, 2010;Sellami et al, 2012). The concentration of the identified compound was computed based on the percentage of the relative peak area (%).…”
Section: Essential Oils Analyses By Gc-ms Methodsmentioning
confidence: 99%
“…Fig. 3 demonstrates the calibration curve RI-RT used for calculation of RIs, and the retention data from the database for the components from the hit lists for several selected peaks [63]. As was indicated above, the RI of target components from the database should correspond to the experimentally determined RI within experimental error limits.…”
Section: Application Of Retention Indices In Identificationmentioning
confidence: 99%
“…Babushok and Andriamaharavo [63] used a large RI database (NIST GC-MS database) for analysis of ylang-ylang essential oil. They suggested using the calibration [RI = f(t r )] for removing false-positive identifications.…”
Section: Application Of Retention Indices In Identificationmentioning
confidence: 99%
“…For example, Lee et al [6] reported that the mass spectra of four farnesol isomers have very similar mass spectra, while the retention indices of them are different from each other with high confidence interval. For these reasons, retention indices have been used for high accuracy compound identification [711]. Smith et al [9] suggested compound identification using combined spectral similarity measure and retention index deviation.…”
Section: Introductionmentioning
confidence: 99%
“…Schauer et al [10] created a platform for mass spectral and retention time index libraries for metabolite identification. Babushok et al [11] comprehensively evaluated the retention indices for 505 frequently reported plant essential oil components using a large retention index database. AMDIS software also provided an application to use retention index database with mass spectrum for identification [1].…”
Section: Introductionmentioning
confidence: 99%